Locating the built environment within existing empirical models of climate change and mental health: protocol for a global systematic scoping review - Maree Teesson; Ross Bailie; Scarlett Smout; Emma L Barrett; Lexine A Stapinski; Lyrian Daniel; Marlee Bower; Lauren M Scott; Amarina Donohoe-Bales; Gareth Bryant; Edward Jegasothy; Shamila Haddad; et al. (BMJ Open)
Introduction Where a person lives, the characteristics of their housing and neighbourhood environment influence their exposure to climate-related hazards and vulnerability to associated mental health impacts. This suggests that the built environment may be a promising focus for integrated policy responses to climate change and public mental health challenges. However, few empirical studies have focused on the role of the built environment as an important mediator of climate-attributable mental health burden. The proposed scoping review seeks to identify and synthesise existing conceptual models and frameworks linking climate change to mental health via built environment pathways. We aim to provide a preliminary overview of the housing and neighbourhood pathways through which climate change may impact mental health, which will inform future empirical work in this emerging area of research.Methods and analysis A systematic scoping review of the global peer-reviewed and grey literature will be conducted in accordance with Arksey and O’Malley’s methodological framework and Joanna Briggs Institute recommendations. Included articles must present a conceptual model or framework incorporating relevant built environment pathways through which climate change may impact mental health and well-being. Relevant models and frameworks will be identified through systematic searches (for English-language reports) of Medline, PsycINFO, Embase, Scopus, Web of Science and grey literature databases. Two reviewers will independently screen the article titles, abstracts and full texts, with conflicts resolved by a third reviewer. Data extraction will occur using a predefined template. The presentation of findings will conform to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Extension for Scoping Reviews, including a narrative synthesis of the role of housing and neighbourhood factors in the relationship between climate change and mental health, as identified from the existing literature. The review will lay essential foundations for future empirical research and place-based policy responses to the mental health consequences of a changing climate.Ethics and dissemination The scoping review will be a secondary analysis of published data, for which ethics approval is not required. The results will be disseminated through a peer-reviewed publication and targeted distribution to stakeholders involved in climate change, built environment and health research and policymaking.Study registration Open Science Framework: doi.org/10.17605/OSF.IO/XR74C.